Influence of bee honey on water activity indicators and model ph samples in the process of drying-maturation of fermented meat products - Strashynskyi, Igor; Pasichnyi, Vasyl; Romazan, Alexandr (My University, 2021)
A feature of modern sausage production is the intensification of technological processes. Given the dynamics of the decline in the purchasing power of the population of Ukraine, which coincides with the global trend, the development of innovative products and recipes for meat products with improved organoleptic properties is becoming increasingly important. This primarily applies to delicacies of meat products, namely fermented meat products (smoked and cured sausages), which differ from other types of sausages in dense consistency, specific aroma, pleasant taste, have high biological and energy value, retain high quality for a long shelf life. Особливістю сучасного ковбасного виробництва є інтенсифікація технологічних процесів. Враховуючи динаміку зниження купівельної спроможності населення України, яка збігається із загальносвітовою тенденцією, все більшої актуальності набуває розробка інноваційних продуктів і рецептур м’ясних виробів з покращеними органолептичними властивостями. В першу чергу це стосується м’ясних делікатесів, а саме ферментованих м’ясних виробів (копчених та в’ялених ковбас), які відрізняються від інших видів ковбас щільною консистенцією, специфічним ароматом, приємним смаком, мають високу біологічну та енергетичну цінність, тривалий час зберігають високу якість. термін придатності.
Keywords: кафедра технології м’яса і м’ясних продуктів; інтенсифікація технологічних процесів; м’ясні делікатеси; бджолиний мед; ферментировані м’ясні продукти; intensification of technological processes; meat delicacies; bee honey; fermented meat products